Large Eddy Simulation of Flow over a Cylinder Using High-Order Spectral Difference Method (Advances in Applied Mathematics and Mechanics, 2019)
Large eddy simulation of the flow over a circular cylinder at Reynolds number ReD=2580 has been studiedwith a high-order unstructured spectral difference method. Grid and polynomial refinement studies were carriedout to assess numerical errors. The mean and fluctuating velocity fields in the wake of a circular cylinder werecompared with PIV experimental measurements. The numerical results are in excellent agreement with the experimentaldata for both the mean velocity and Reynolds stresses using the high-order SD scheme. Other wake characteristicssuch as the recirculation bubble length, vortex formation length and maximum intensity of the velocity fluctuationshave also been predicted accurately. The numerical simulations demonstrated the potential of the high-order SD methodin accurate large eddy simulation of physically complex problems.